INCEIF deputy president Syed Othman retires - Reserve, The Malaysian (themalaysianreserve, 2017)
INTERNATIONAL Centre for Education in Islamic Finance(INCEIF) deputy president academic Prof Datuk Dr Syed Othman Alhabshi has retired effective July 20, confirmingan earlier report by The Malaysian Reserve. In a statement , INCEIF, said Ezamshah Ismail, its dean of School of Professional Studies, has been named the actingdeputy president academic, in addition to his current role at the university.